2009
DOI: 10.2501/s0265048709200916
|View full text |Cite
|
Sign up to set email alerts
|

Memory and perception of brand mentions and placement of brands in songs

Abstract: International audienceAlthough brand placement in movies and TV series has attracted significant interest from researchers and practitioners, little is known about the financed insertion of brands in songs. However, evidence is growing that this kind of placement could be of interest for addressing certain types of target audience. This article sheds light on this new form of communication, and highlights its interest for advertisers. It also studies its effectiveness. Based on a web survey, the paper analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 31 publications
3
26
0
1
Order By: Relevance
“…These findings are consistent with the results of previous studies which have shown the positive impact of such placements on brand awareness and product placement recall and recognition (Russell, 1999;Russell 2002;Law & Braun, 2000;Gupta & Lord, 1998;Brennan et al, 1999;Steortz, 1987;Brennan & Babin, 2004;Delattre & Colovic, 2009;Johnstone & Dodd, 2000;Yang & Roskos-Ewoldsen, 2007;Cowley & Barron, 2008;Lehu & Bressoud, 2009). …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are consistent with the results of previous studies which have shown the positive impact of such placements on brand awareness and product placement recall and recognition (Russell, 1999;Russell 2002;Law & Braun, 2000;Gupta & Lord, 1998;Brennan et al, 1999;Steortz, 1987;Brennan & Babin, 2004;Delattre & Colovic, 2009;Johnstone & Dodd, 2000;Yang & Roskos-Ewoldsen, 2007;Cowley & Barron, 2008;Lehu & Bressoud, 2009). …”
Section: Discussionsupporting
confidence: 83%
“…The prominence of placed brands is the second factor which has been found to improve cognitive effects. Previous research has indicated that prominent placements are better recalled and better recognized than subtle placements (Brennan, Dubas, & Babin, 1999;Gupta & Lord, 1998;Weaver & Oliver, 2000;Cowley & Barron, 2008;Delattre & Colovic, 2009;Lehu & Bressoud, 2009, Bressoud et al, 2010Wilson & Till, 2011). The third important element which improves brand memory is high connection to the plot.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cowley and Barron (2008) consider placements to be prominent when those placements "(1) were connected to the plot, (2) were mentioned more than once or were on the screen for more than five seconds, and (3) were either audio or audiovisual," while subtle placements "were (1) visual, (2) not 48 N. S. FERGUSON AND J. N. BURKHALTER related to the plot, and (3) seen only briefly" (92). Scholars like de Gregorio and Sung (2009) and Delattre and Colovic (2009), however, argue that that prominence must be conceptualized differently for auditory-only content. In their studies, prominence is operationalized based on the frequency and repetition of mentions.…”
Section: Literature Review Brand Placement Definedmentioning
confidence: 95%
“…Gupta and Gould, 1997) although it is also common to see brands placed in computer games, books, stage plays and popular music (e.g. Delattre and Colovic, 2009). Moreover, most extant definitions emphasise that placements are 'paid for' by the advertiser but this ignores two important issues.…”
Section: Product Placement Researchmentioning
confidence: 99%